Significance of dyslipidemia for primary open-angle glaucoma - C. Erb; A. Kim (Российский офтальмологический журнал, 2022)
Reduction of intraocular pressure is currently considered as the main strategy to stop or slow down the progression of glaucomatous optic neuropathy. However, this goal is achieved in only 1 in 7 patients with primary open-angle glaucoma (POAG). Therefore, it is important to determine further risk factors that can be therapeutically influenced. One example of such risk factors is lipid metabolism disorders. Material and methods. Literature search in PubMed using the queries “primary open-angle glaucoma” and “dyslipidemia” limiting oneself to the period from 2000 to 2021. Results. POAG is currently considered to be a systemic neurodegeneration with neuroinflammation at the forefront. Oxidized low density lipoprotein (oxLDL) acts as a free radical (so-called bioactive lipid) with pro-inflammatory properties and promotes glaucomatous neuroinflammation. Conclusion. In addition to a personalized targeted pressure-oriented intraocular pressure reduction, LDL-associated lipid metabolic disorders should be corrected in every POAG patient. LDL cholesterol below 100 mg/dl (2.6 mmol/l) in the blood is the critical threshold level.